MRI lesions can often precede trigeminal neuralgia symptoms by years in multiple sclerosis. Issue 3 (17th November 2022) - Dilwali, Sonam; Mark, Ian; Waubant, Emmanuelle
Abstract : Background: Understanding when multiple sclerosis (MS) lesions become clinically symptomatic may provide insight into disease pathophysiology. Our objective was to temporally associate lesion formation and trigeminal neuralgia (TN) symptom onset in MS. Methods: This is a retrospective case series of patients with MS, analysing time difference between TN symptom onset and oldest MRI showing a correlative lesion. Results: For the 26 patients with MS, a correlative lesion was noted on MRI on average 5±4 years prior to TN symptom onset; 57% had primary or secondary progressive MS. Conclusions: TN lesions can be present years prior to symptom onset, suggestive of alternative explanations than typical relapses. This phenomenon may hint at alternative pathophysiology of progressive MS in comparison to relapsing-remitting MS.